POTENTIALS OF WATER LETTUCE MULCH ON GERMINATION AND PRELIMINARY GROWTH OF Jatropha Curcas - Offor, U. Stephen; Wuradarn, M. (European Scientific Journal, ESJ, 2015)
The potentials of water lettuce mulch as an aquatic macrophytes in enhancing germination and preliminary growth of J. curcas was investigated at the teaching and research farm of Ignatius Ajuru University of Education, Port- Harcourt. The experiment was laid out in a randomized complete block design (RCBD), with three treatments, replicated thrice. The treatments consist of 100g, 50g of water lettuce mulch and control. Data was obtained through direct observation and measurement computed through statistical means. Results from Data analysis shows that water lettuce mulch applied at the rate 100g and 50g gave significant increase in germination, plant height, number of leaves and root of J, curcas compared to control.